Antioxidant Profiles of Chitosan-Alginate Films with Addition of Moringa oleifera Leaf Extract for Active Packaging - Riyandari, Baiq Amelia; Multazam, Multazam (Indonesian Journal of Chemical Research, 2023)
This research aims to study the antioxidant activity of chitosan-alginate films by adding Moringa oleifera leaf extract. These films will be applied as active packaging for food. This research was initiated by the extraction of Moringa oleifera leaves. The Moringa oleifera leaves extract was prepared maceration and soxhletation techniques using distilled water as a solvent. The maceration method is resulting the yield 6.97%, while the yield of extract from the soxhletation method was 8.57%. After the extraction process, screening phytochemicals of Moringa oleifera leaves extract was tested to identify secondary metabolite compounds. Screening phytochemicals of the extract showed that Moringa oleifera extract contains alkaloids, flavonoids, tannins, and saponins. Synthesizing of films was conducted at room temperature through a homogenization technique using a hot plate stirrer. The variations of final concentrations of extract were 0% (film A0), 0.50% (film A1), 0.75% (film A2), and 1.00% (film A3). Based on the antioxidant activity test using DPPH, the % RSA value of films with the addition of extract from soxhletation method was higher than films with the addition of extract from the maceration technique. The highest percentage of RSA value was 43.65% from A3 film with the extract's final concentration of 1.00%.